Social Studies Educators’ Evaluations About Children’ s Delinquency and Preventive Measures - Öngören, Hakan; Yilmaz, Fatih (Journal of Qualitative Research in Education, 2025)
Juvenile delinquency is now a major social problem and has become not only a national but also a global issue. In fact, children are at risk of becoming involved in crime due to various factors (economic, family and social). The most important task at the point of taking protective measures by identifying the situation of children before they are drawn into crime falls to educators. The group of participants in the study conducted for this purpose consisted of 18 social studies educators working in the Ministry of National Education and Higher Education Institutions. The data obtained through a semi-structured interview form was designed as a case study from qualitative research approaches, as it aimed to understand the reasons that lead to juvenile delinquency and the measures that should be taken based on the opinions of social studies educators. The data were interpreted by dividing them into codes, categories and themes according to the content analysis technique and MAXQDA 24 was used in this process. According to the results of the research, the participants stated that role models and parental attitudes among the family factors and peer bullying among the social environment factors have an important effect among the reasons that push juvenile delinquency; the family should show interest in order to prevent the child from being involved in crime; the current protective measures for juvenile delinquency are insufficient. The Ministry of the Interior should prioritize at-risk groups and organize seminars on crime prevention.